The Experience of Speech-Language Therapists with Telepractice for Adults and Older Adults During the COVID-19 Pandemic in Chile - Mohammad, Jenan; Matus-Rosas, Paulina; Quezada, Camilo (Revista Chilena de Fonoaudiología, 2024)
Telepractice, as a strategy for remote care, has a long history in the field of speech-language therapy in developed countries, and gained sudden prominence in Chile due to the COVID-19 pandemic. This study aims to characterize the teletherapy provided to adults and older adults by speech-language therapists during the healthcare crisis. A survey was administered to 38 speech-language therapists. Subsequently, the responses were analyzed by topic, after which descriptive statistics were used in the form of Fischer’s exact tests. Most patients were between 60 and 79 years old and enrolled in Fondo Nacional de Salud (National Health Fund). Significant barriers were identified, related to digital literacy, access to a device, and the environment of the patient. However, facilitators were also highlighted, including ongoing access to therapy, reduced travel times, and the ability to work with co-therapists. When comparing public and private sector care, significant differences were found in the quality of the environment (p=0.03) and digital literacy (p=0.008). In conclusion, participants noted more barriers than facilitators in implementing telepractice during the pandemic. Nevertheless, they consider it an effective tool that can complement in-person care. It is crucial to develop best practices for telepractice, considering barriers related to material resources that may limit access. Additionally, this modality should be included in the training of speech-language therapists.